COMPARASION OF LUPIN MEAL BASED DIETS COST EFFICIENCY FOR JUVENILE Penaeus monodon TESTED UNDER POND CONDITIONS - Agung Sudaryono (JOURNAL OF COASTAL DEVELOPMENT, 2004)
A comparison of the cost efficiency of the formulated diets for juvenile Penaeus monodon in which fish meal or fish meal and soybean meal mixture were substituted with lupin (Lupinus angustifolius) meal at different levels has been conducted and is described in this study. The method used in the study was to estimate the relative economic performance for each dietary treatment using cost efficiency analysis equations. All diets containing different levels of lupin meal (0-30% and 0-48%) were compared in terms of total feed cost to determine the most cost-effective lupin meal based diet for juvenile Penaeus monodon reared in pens under pond conditions. The results show that inclusion of lupin meal at a level of 30% that substitute 75% of fish meal protein in D4 formulation saved 18% in price in Australia and 11% in price in Indonesia when compared with D1 with no lupin meal. Diet D9 including 48% of lupin meal to substitute 75% of a mixture of fish meal and soybean meal saved 21% in price in Australia and 14% in price in Indonesia when compared with D6 with no lupin meal. it is concluded that diets D4 and D9 containing 30% and 48% dehulled lupin (L. angustifolius) meal as a replacement of 75% protein of fish meal and the mixture of fish meal and soybean meal, respectively can be considered as the most economical and profitable diets with an acceptable level of production for semi-intensive pond culture of P. monodon stocked at a level of 10 animals/m2.